Scaling of Convective Heat Transfer Enhancement Due to Flow Pulsation in an Axisymmetric Impinging Jet - MURRAY, DARINA; PERSOONS, TIM (My University, 2013)
Impinging jets are widely used to achieve a high local convective heat flux, with applications in high power density electronics and various other industrial fields. The heat transfer to steady impinging jets has been extensively researched, yet the understanding of pulsating impinging jets remains incomplete. Although some studies have shown a significant enhancement compared to steady jets, others have shown reductions in heat transfer rate, without consensus on the heat transfer mechanisms that determine this behavior. This study investigates the local convective heat transfer to a pulsating air jet from a long straight circular pipe nozzle impinging onto a smooth planar surface (nozzle-to-surface spacing 1  H / D  6, Reynolds numbers 6000  Re  14,000, pulsation frequency 9Hz  f  55Hz, Strouhal number 0.007  Sr = fD / U m  0.1). A different behavior is observed for the heat transfer enhancement in (i) the stagnation zone, (ii) the wall jet region and overall area-average. Two different modified Strouhal numbers have been identified to scale the heat transfer enhancement in both regions: (i) Sr ( H / D ) and (ii) SrRe 0.5 . The average heat transfer rate increases by up to 75-85% for SrRe 0.5  8 ( Sr = 0.1, Re = 6000), independent of nozzle-to-surface spacing. The stagnation heat transfer rate increases with nozzle-to-surface distance H / D . For H / D = 1 and low pulsation frequency ( Sr < 0.025), a reduction in stagnation point heat transfer rate by 13% is observed, increasing to positive enhancements for Sr ( H / D ) > 0.1 up to a maximum enhancement of 48% at Sr ( H / D ) = 0.6.
PUBLISHED
Keywords: impinging jet; pulsating flow; hot spot; high density; electronics cooling; boundary layer redevelopment.; boundary layer redevelopment.; electronics cooling; high density; hot spot; pulsating flow; impinging jet; Smart & Sustainable Planet; Telecommunications